The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1002/anie.201503042
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐Catalyzed Intermolecular Asymmetric Propargylic Dearomatization of Indoles

Abstract: The first copper-catalyzed intermolecular dearomatization of indoles by an asymmetric propargylic substitution reaction was developed. This method provides a highly efficient synthesis of versatile furoindoline and pyrroloindoline derivatives containing a quaternary carbon stereogenic center and a terminal alkyne moiety with up to 86 % yield and 98 % ee.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 149 publications
(24 citation statements)
references
References 73 publications
0
24
0
Order By: Relevance
“…[1] Diverse elegant methods extensively complemented the fields of traditional coupling reactions and provided widely applicable approaches for new bond formation. [2] Efficient oxidative coupling protocols for functionalized indoles have been developed by the groups of Harran, [3] Danishefsky, [4] Trost, [5] Nicolaou, [6] Overman, [7] Muniz, [8] MacMillan, [9] Xiao, [10] Lei, [11] Vincent, [12] You, [13] Stephenson, [14] and others. [15] While, the synthetic utility of catalytic oxidative coupling cyclization for construction of complex benzofuroindolenines has not been fully developed.…”
Section: Abstract: Catalytic Oxidative Coupling Cyclization; Benzofurmentioning
confidence: 99%
“…[1] Diverse elegant methods extensively complemented the fields of traditional coupling reactions and provided widely applicable approaches for new bond formation. [2] Efficient oxidative coupling protocols for functionalized indoles have been developed by the groups of Harran, [3] Danishefsky, [4] Trost, [5] Nicolaou, [6] Overman, [7] Muniz, [8] MacMillan, [9] Xiao, [10] Lei, [11] Vincent, [12] You, [13] Stephenson, [14] and others. [15] While, the synthetic utility of catalytic oxidative coupling cyclization for construction of complex benzofuroindolenines has not been fully developed.…”
Section: Abstract: Catalytic Oxidative Coupling Cyclization; Benzofurmentioning
confidence: 99%
“…Over the past decades, great progress has been made on the Ru‐ and Cu‐catalyzed propargylic substitution reactions via the metal‐allenylidene complexes . As our ongoing efforts towards the development of catalytic asymmetric dearomatization reactions, we envisioned that a copper‐catalyzed asymmetric propargylic dearomative [4+2] cycloaddition of simple substituted indoles with a copper‐allenylidene amphiphilic intermediate would afford the tetracyclic core structure of indole alkaloids communesins A‐H and perophoramidine (Scheme ). Of particular note, Xiao and co‐workers successfully disclosed the first copper‐catalyzed asymmetric propargylic formal [4+1] cycloaddition reaction with sulfur ylides .…”
Section: Figurementioning
confidence: 99%
“…Further evaluation of the concentration( entries 7-11) of 1a revealed that c = 0.2 mol L À1 was optimal in terms of yield (entry 8). Pd 2 (4-OMe-dba) 3 was ab etter palladium source than Pd 2 dba 3 and [Pd(allyl)Cl] 2 (entries 12 and 13). [10] Furthermore, some additives were tested.…”
mentioning
confidence: 99%
“…[2] Notably,t ransitionmetal-catalyzed allylic dearomatization reactions of indoles have witnessed significant progresses in the past decade. [3,4,5] Recently,w er ealized the construction of fused indolenine skeletons in ac ascadef ashion. [6] In 2014, the Rawal group and we independently reported an intermolecular cascade dearomatization reactiono fi ndole-based bisnucleophiles with propargyl carbonate, leading to aseries of spiroindolenines andspiroindolines.…”
mentioning
confidence: 99%
See 1 more Smart Citation